(untitled) (Research, Society and Development, 2023)
This study aimed to foster debate on the health system in Brazilian prisons, highlighting its importance and challenges. The used methodology was the qualitative research, having as data collection the bibliographic survey. The most relevant conclusions are issues inherent to health that have been neglected in the Brazilian penitentiary system, motivated by a series of structural deficiencies, among them: overcrowding, lack of minimum structures for clinical care, as well as permanent health units. Through the literature review, it was found that although there are public policies aimed at the issue, they are still insufficient in the face of the extensive population demand and the inadequate conditions of prisons that not only can aggravate certain clinical conditions, but also be the very cause that gave rise to the disease. With a view to creating adequate conditions for health and medical care, public health policies need to encourage the incorporation, in the health units of Brazilian prisons, of a healthy environment and a culture of care and rehabilitation; plus adequately supervised care, including basic social care for prisoners.